Contents of endogenous brassinosteroids and the response to drought and/or exogenously applied 24-epibrassinolide in two different maize leaves - Marková, Hana; Tarkowská, Danuše; Čečetka, Petr; Kočová, Marie; Rothová, Olga; Holá, Dana (Frontiers in Plant Science, 2023)
Exogenously applied brassinosteroids (BRs) improve plant response to drought. However, many important aspects of this process, such as the potential differences caused by different developmental stages of analyzed organs at the beginning of drought, or by BR application before or during drought, remain still unexplored. The same applies for the response of different endogenous BRs belonging to the C27, C28-and C29- structural groups to drought and/or exogenous BRs. This study examines the physiological response of two different leaves (younger and older) of maize plants exposed to drought and treated with 24-epibrassinolide (epiBL), together with the contents of several C27, C28-and C29-BRs. Two timepoints of epiBL application (prior to and during drought) were utilized to ascertain how this could affect plant drought response and the contents of endogenous BRs. Marked differences in the contents of individual BRs between younger and older maize leaves were found: the younger leaves diverted their BR biosynthesis from C28-BRs to C29-BRs, probably at the very early biosynthetic steps, as the levels of C28-BR precursors were very low in these leaves, whereas C29-BR levels vere extremely high. Drought also apparently negatively affected contents of C28-BRs (particularly in the older leaves) and C29-BRs (particularly in the younger leaves) but not C27-BRs. The response of these two types of leaves to the combination of drought exposure and the application of exogenous epiBL differed in some aspects. The older leaves showed accelerated senescence under such conditions reflected in their reduced chlorophyll content and diminished efficiency of the primary photosynthetic processes. In contrast, the younger leaves of well-watered plants showed at first a reduction of proline levels in response to epiBL treatment, whereas in drought-stressed, epiBL pre-treated plants they were subsequently characterized by elevated amounts of proline. The contents of C29- and C27-BRs in plants treated with exogenous epiBL depended on the length of time between this treatment and the BR analysis regardless of plant water supply; they were more pronounced in plants subjected to the later epiBL treatment. The application of epiBL before or during drought did not result in any differences of plant response to this stressor.